Human Papillomavirus (HPV) in Rural Adolescent Females: Knowledge, Protected Sex, and Sexual Risk Behaviors - Janet F. Wang; Patricia S. Simoni; Ying Wu (Rural Nurse Organization; Binghamton University, 2006)
Reduction of cervical cancer morbidity/mortality relies on prevention and early detection of human papillomavirus (HPV). This study examined HPV knowledge, attitudes toward protected sex, and sexual risk behaviors among rural female adolescents, through cross-sectional survey of a convenience sample (n = 159). Data analysis, via the Statistical Package for Social Studies (SPSS), identified a sexually active sample (64%) with limited knowledge regarding effective sexual protection or HPV. Subjects living with both parents were (a) less knowledgeable about HPV than those living with single parents (b = -2.05, p = 0.035), as well as (b) less likely to be sexually active than those in other living arrangements (55% vs 77%, p = .0082). These findings suggest that the adolescent-parent relationship warrants further exploration in increasing knowledge regarding risk and reducing exposure to HPV.